Analisis hubungan kredit mikro dan pembangunan sahabat dalam projek ekonomi skim Amanah Ikhtiar Malaysia (AIM) - Mohd. Saifoul Zamzuri, Noor (2016)
Most of the past studies on the impact of Amanah Ikhtiar Malaysia (AIM) microcredit scheme have generally concluded that the scheme has been successful in increasing the income and quality of life of the borrowers. However, in these studies income is examined in aggregate, i.e. household income that covers income from the microcredit project activities and also income from other sources. Thus, while there is an increase in income among the borrowers, it is possible that the increase might not come solely from the microcredit project activities. Disaggregating microcredit project activities income from other sources is therefore important. Past studies also failed to explain the mechanisms through which microcredit affects income, directly or indirectly through mediation variables. Furthermore, previous studies seemed to overlook the impact of microcredit on employment opportunities and productivity, which might be significant. Thus, the objectives of this study are to evaluate the impact of microcredit on income of the borrowers from the microcredit project activities, to analyse the mechanisms through which microcredit affects income, i.e. the mediating effect of human capital, social capital and physical capital, to analyse the impact of microcredit on employment opportunities and productivity, and to analyse the impact of microcredit on poverty and income inequality. For this purpose, a total of 495 borrowers who have been involved in non-farm activities and receive AIM’s microcredit scheme were selected for analysis. Multivariate regression, structural equation modelling and Foster Greer Thorbecke index were employed in the analysis. The findings of the study show that microcredit has a significant impact on the income, even when the income was segregated. The results also interestingly reveal that the impact of microcredit on the income via mediating factors which are human capital, social capital and physical capital is indirect. Furthermore, microcredit also provides a significant impact on the employment, productivity, and reduction in poverty and inequality among the borrowers. Thus, with a complete and systematic financing package, the development of participants in the project activities can be strengthened.